2017
DOI: 10.24200/sci.2017.20016
|View full text |Cite
|
Sign up to set email alerts
|

An improved model and a heuristic for capacitated lot sizing and scheduling in job shop problems

Abstract: This paper studies the problem of capacitated lot-sizing and scheduling in job shops with a carryover setup and a general product structure. After analyzing the literature, the shortcomings are easily realized; for example, the available mathematical model is unfortunately not only non-linear but also incorrect. No lower bound and heuristic is developed for the problem. Therefore, we first develop a linear model for the problem on-hand. Then, we adapt an available lower bound in the literature to the problem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…There is a plenty of different heuristic algorithms (including Tabu search, GA, SA, PSO, Ant and Bee colony, and etc.) among which SA and Tabu search algorithms based on their merits are employed extensively for optimization of different problems and processes [13][14][15][16][17][18]. Easy to program and converge fast are the significant advantages of using TS algorithm.…”
Section: Designing the Solution Methodsmentioning
confidence: 99%
“…There is a plenty of different heuristic algorithms (including Tabu search, GA, SA, PSO, Ant and Bee colony, and etc.) among which SA and Tabu search algorithms based on their merits are employed extensively for optimization of different problems and processes [13][14][15][16][17][18]. Easy to program and converge fast are the significant advantages of using TS algorithm.…”
Section: Designing the Solution Methodsmentioning
confidence: 99%
“…JSSP is a NP-hard problem [42]. Exact methods exhibit impractical computational times for medium and large instances, therefore, it is inevitable to apply proper and efficient solution methods for solving these types of problems.…”
Section: -5 Solution Representationmentioning
confidence: 99%
“…Although the studies in the literature have performed better than the heuristics, they have been found to be less performance than the meta-heuristic ones. It has been stated that the issue is an open area to develop [40]. For this purpose, a new model is proposed in order to find solutions to large-scale problems and to make the obtained results compete with other metaheuristics.…”
Section: The Best Parameter Levels According To the Size Of The Problemmentioning
confidence: 99%